Risk, precaution, and regulation in chemical search and innovation: The case of the EU REACH legislation - Gianluca Biggi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2023)
This study investigates the impact of the introduction of the European chemical regulation (the EU REACH legislation) on chemical search and innovation by focusing on the knowledge recombination processes leading to the generation of inventions. Using a novel dataset of patents and chemical structures contained therein over the period 1978-2016, this study readapts established patent indicators to capture the complexity, novelty, and novelty in recombination of the inventive activities as a result of the chemical regulation. The separate effect of the chemical regulation reflected in +39.8% of compounds per patent, +23% of new compounds per patent, and +2% of newer recombinations of compounds per patent is supported by the Propensity Score Matching estimations. The positive and significant effect of chemical regulation on compound patenting supports prior scholarly work on the idea that regulations by altering the search space, influence the rate and intensity of technological search and innovation.
Keywords: O38; 330; Chemical inventions; Patent data; Regulation; Knowledge recombination